Developing Abstract Representations of Passives: Evidence From Bilingual Children’s Interpretation of Passive Constructions - Nicoladis, Elena; Sajeev, Sera (Frontiers in Psychology, 2020)
According to usage-based theories, children initially acquire surface-level constructions and then abstract According to usage-based theories, children initially acquire surface-level constructions and then abstract representations. If so, bilingual children might show lags relative to monolingual children early in acquisition, but not later on, once they rely on abstract representations. We tested this prediction with comprehension of passives in three- to six-year-old children: French-English bilinguals and English monolinguals. As predicted, younger bilingual children tended to be less accurate than monolingual children. In contrast, the older bilingual children scored equivalently to monolinguals, despite less exposure to English. When the children made errors, the bilingual children were more likely to interpret the subject as the agent of the action than the monolingual children. These results are consistent with the argument that children develop increasingly abstract representations of linguistic constructions with usage. They further suggest that bilingual children might catch up with monolingual through use of selective attention and/or a semantic bias.